Sentinel laboratory compliance with best practices in Burkina Faso's antimicrobial resistance surveillance network - Dame Yenyetou; Emmanuel Zongo; Emilie Dama; Merci Muhigwa; Issouf Sanou; Charles Sawadogo; Soumaya Ouangraoua; Ibrahim Sangare; Abdoulaye Nikiema; Anicet G. Dahourou; Abdoul S. Ouedraogo (AOSIS, 2024)
Background: Standardising procedures is the best way to harmonise and strengthen the quality of laboratory-based antimicrobial resistance surveillance. Since 2018, Burkina Faso has developed and disseminated the national manual of procedures for performing antibiotic susceptibility tests in sentinel laboratories within its national antimicrobial resistance surveillance network. Objective: Our study aimed to assess these sentinel laboratories' compliance with good practices for antibiotics susceptibility tests. Methods: Four teams evaluated the antimicrobial resistance sentinel sites laboratories throughout Burkina Faso from 19 to 28 September 2022. Eighteen out of 19 sentinel laboratories were evaluated. A four-member technical committee designed and validated the evaluation tool composed of three Microsoft Excel sheets. The evaluation emphasised quality controls for culture media, antibiotic discs and compliance with antimicrobial susceptibility testing procedures by the laboratories. Excel software was used for data recording and graphs and table design. The free R software version 4.2.0 was used for descriptive statistics. An overall score below 80% was considered noncompliance. Results: Most (83.33%) of the sentinel laboratories conducted at least one quality control activity for culture media, and 66.67% conducted at least one quality control activity for antibiotic discs. Over three-quarters (76.47%) of the laboratories were more than 80% compliant with the modified Kirby Bauer antimicrobial susceptibility testing method. Conclusion: The evaluation revealed the noncompliance of sentinel laboratories with the national procedure manual, particularly in the quality control component. What this study adds: This study has provided baseline data on the sentinel laboratories' compliance with the national antimicrobial susceptibility testing procedures manual, particularly in areas performing quality control checks or meeting quality indicators for culture media and antibiotic discs.